Developing Short-f orrn Measures of Oral Health-related Quality of Life - David Locker, PhD (Blackwell Synergy, 2002)
Using the item-impact method, we developed an alternative shortform Oral Health Impact Profile (OHIP) that has good psychometric properties and minimal floor effects